Analisis Faktor Yang Mempengaruhi Profitabilitas Pada Sektor Perbankan - Giovani Virza Amallia; Suhartono Suhartono (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
Background – Bank can achieve their objective in making a profit by considering some factors. Among the factors considered are factors attached to the internal bank. Among other things, through the management of operational activities, it will impact the bank’s performance over the resulting profitability ratios. Aim – The purpose of this study was to examine the ratio of Loan to Deposit Ratio, NPL, Bank Size, and Good Corporate Governance partially to Return-On-Asset in banking sector. Design / methodology / approach – The population used in this study is banking in Indonesia. In this study using purposive sampling technique. The data source of this research uses quantitative secondary data. The analysis technique used in this research is multiple linear regression model. Findings – The results of this show that Loan to Deposit Ratio has a significant positive effect on Return On Asset while the Non-Performing Loan ratio has an negative significant effect on Return On Asset. The Bank Size and Good Corporate Governance ratios have a insignificant negative influence on Return On Asset. Research implication – Based on the results of tests that have been carried out previously, this study has managerial implications in reviewing what factors can increase profitability for Commercial Banks of Business Category 2. Limitations – The research sample is limited to BUKU 2 only. The research period used is limited to 2015-2019. The factors that influence the Return On Asset are limited to internal factors.